Assessment of Teachers' Perception On Modern Technology (ICT) And Communication Efficiency: A Case Study - Olorunsola, Stephen; Ogwueleka, Francisca (International journal of education and development using information and communication technology, 2021)
Modern technology has brought about a revolution in the communication process. The revolution started with the emergence of desktop computers in the 1980's. Today, the Internet and social media have brought about a 360-degree change in the communication process. The purpose of this study is to examine the perception of secondary school teachers in Kaduna State, Northern Nigeria on the impact of ICT deployment for communication efficiency in the teaching and learning process. The population for the study was teachers in five secondary schools in the state. Simple random sampling was used, and 120 teachers were chosen for the sample. Three-way cross tabulation (crosstabs) and means were used to show association between variables and analysis of the research questions. The results from this study show that ICT media such as the computer and the Internet, have a significant impact on communication efficiency in the teaching and learning process by facilitating clarity, ease, speed, security and prompt feedback in the communication process.